2007
DOI: 10.1093/ndt/gfm503
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-7 delays podocyte injury due to high glucose

Abstract: BMP-7 may confer resistance to hyperglycaemic injury via synaptopodin and podocin suggesting novel BMP7 therapies for diabetic glomerulosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…In addition to the inhibitory effect on MMP expression, BMP-7 possibly inhibits the progression of glomerular pathogenesis in Col4a3 -/-mice at multiple steps. BMP-7 reduces the damage in podocytes (20,41,42) and mesangial cells (43)(44)(45) and attenuates the expression of inflammatory cytokines (46) and apoptosis in several types of cells (12,41). Antagonizing the beneficial effects of BMP-7 by USAG-1 might enhance these injuries and accelerate glomerular pathogenesis in Alport syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibitory effect on MMP expression, BMP-7 possibly inhibits the progression of glomerular pathogenesis in Col4a3 -/-mice at multiple steps. BMP-7 reduces the damage in podocytes (20,41,42) and mesangial cells (43)(44)(45) and attenuates the expression of inflammatory cytokines (46) and apoptosis in several types of cells (12,41). Antagonizing the beneficial effects of BMP-7 by USAG-1 might enhance these injuries and accelerate glomerular pathogenesis in Alport syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In streptozotocin-induced diabetic rats, renal expression of BMP-7 was decreased by more than 90%, and this was accompanied by downregulation of the BMP type II receptor and the type I receptor ALK2 (44). Decrease of BMP-7 expression was also evidenced in mouse podocytes cultured under high glucose, and in renal biopsies of patients with diabetic nephropathy (45,46). Thus far, the latter study is the only report available demonstrating decrease of BMP-7 expression in human patients.…”
Section: Bmp-7 Expression In Renal Fibrosismentioning
confidence: 99%
“…Other protective effects of BMP-7 in proximal tubular epithelial cells include inhibition of TGF-β1 production, decrease of proinflammatory genes and chemoattractants, and inhibition of EMT induced by multiple myeloma light chains (36,50,51). Also in mesangial cells and podocytes, BMP-7 was able to inhibit adverse effects caused by TGFβ1, aldosterone, or high glucose (45,46,52,53). The remarkable potential of BMP-7 even to reverse fibrosis was demonstrated by its ability to induce formation of epithelial cell aggregates in cultures of adult renal fibroblasts, which was accompanied by acquisition of E-cadherin expression and decreased motility, indicating that true mesenchymal-to-epithelial transition (MET) might also be achieved (54).…”
Section: In Vitro Antifibrotic Effects Of Bmp-7 In Renal Cellsmentioning
confidence: 99%
“…Podocytes are located on the outer level of the glomerular basement membrane and cover it with their foot processes [8][9][10] , and podocyte dysfunctions are involved in the development of renal damage in various renal disease model rats, such as hypertensive nephropathy, diabetic nephropathy, and nephrotic syndrome [11][12][13] . In in vitro investigations, high glucose loading on cultured podocytes was shown to enhance apoptosis, decrease the mRNA levels of podocyte-related factors, such as synaptopodin and podocin, and downregulate the expression of bone morphogenetic protein (BMP)-7 [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that BMP-7, a BMP subtype, was expressed in podocytes and renal tubular epithelial cells, and exhibited anti-fibrotic and renopro-tective effects in kidney [14,[18][19][20] . Morrissey et al [21] showed that the administration of BMP-7 to unilateral ureteral ligation model rats improved the glomerular filtration rate (GFR) and inhibited renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%